2018
DOI: 10.1016/j.tips.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Radiosensitizers

Abstract: Radiotherapy (RT) is a mainstay treatment for many types of cancer, although it is still a large challenge to enhance radiation damage to tumor tissue and reduce side effects to healthy tissue. Radiosensitizers are promising agents that enhance injury to tumor tissue by accelerating DNA damage and producing free radicals. Several strategies have been exploited to develop highly effective and low-toxicity radiosensitizers. In this review, we highlight recent progress on radiosensitizers, including small molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
423
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(425 citation statements)
references
References 257 publications
0
423
0
2
Order By: Relevance
“…Tumor responses to RT and clinical outcomes depend on the intrinsic repair capacity, oxygenation of the tumor tissue, modulation of the tumor microenvironment, and the activation of the immune response, as well as other factors . Several pharmacological strategies have been exploited to develop effective and minimally‐toxic radiosensitizers including small molecules, macromolecules, and nanomaterials . Preclinical studies demonstrated that ALA administration sensitized glioma, melanoma, and colon adenocarcinoma cells to RT through the generation of PPIX and enhanced ROS that have physico‐chemical interactions with the X‐rays being irradiated into malignant cells .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor responses to RT and clinical outcomes depend on the intrinsic repair capacity, oxygenation of the tumor tissue, modulation of the tumor microenvironment, and the activation of the immune response, as well as other factors . Several pharmacological strategies have been exploited to develop effective and minimally‐toxic radiosensitizers including small molecules, macromolecules, and nanomaterials . Preclinical studies demonstrated that ALA administration sensitized glioma, melanoma, and colon adenocarcinoma cells to RT through the generation of PPIX and enhanced ROS that have physico‐chemical interactions with the X‐rays being irradiated into malignant cells .…”
Section: Discussionmentioning
confidence: 99%
“…Success of TRT depends on many factors: the expression level of the molecular target in the lesion and healthy organs, the nature of the targeting molecule, its biodistribution pattern and excretion pathway, its pharmacokinetics and their matching to the physical properties of radioisotope employed as well as the size of targeted lesions. Taking into account the complexity of mechanisms driving cancer development and progression, it is reasonable to assume that TRT combined with therapies enhancing radiosensitivity should improve treatment outcome …”
Section: Discussionmentioning
confidence: 99%
“…Radiosensitizer is a substance that increases the sensitivity of tumor cells to radiation to improve the effect of radiotherapy. Perfect radiosensitizers specifically increase the sensitivity of tumor cells to radiation, but not of normal cells 4,5 . In recent years, many epidemiological and clinical studies have proved that “selenium,” as an essential trace element in the human body and animals, plays an important role in tumor prevention and treatment 6‐7 .…”
Section: Introductionmentioning
confidence: 99%
“…Perfect radiosensitizers specifically increase the sensitivity of tumor cells to radiation, but not of normal cells. 4,5 In recent years, many epidemiological and clinical studies have proved that "selenium," as an essential trace element in the human body and animals, plays an important role in tumor prevention and treatment. [6][7] However, selenium is rarely used as cervical cancer radiotherapy sensitization agent; therefore, the present study intends to explore the effect of selenocystine (SeC) on the impact of cervical cancer HeLa radiation sensitivity, and the enhancement of cervical cancer radiation sensitivity mechanism has carried on the preliminary discussion, to provide an experimental basis for the research of cervical cancer radiotherapy sensitization agent.…”
mentioning
confidence: 99%